Former Yugoslav Republic of Macedonia : Report on Observance of Standards and Codes; Fiscal Transparency Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This report summarizes the Observance of Standards and Codes on Fiscal Transparency for the Former Yugoslav Republic of Macedonia. It provides an assessment of fiscal transparency practices in the Former Yugoslav Republic (FYR) of Macedonia in relation to the requirements of the IMF Code of Good Practices on Fiscal Transparency based on discussions with the authorities and other organizations and through a fiscal transparency questionnaire. It also provides recommendations for improving fiscal transparency and information on fiscal risks, contingent liabilities, and tax expenditure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet